Neuroinflammation in perioperative neurocognitive disorders: From bench to the bedside. (6th January 2022) - Liu, Yang; Fu, Huiqun; Wang, Tianlong
Abstract: The perioperative neurocognitive disorders (PNDs) are one of the most common complications in elderly patients characterized by various forms of cognitive decline after anesthesia and surgery. Although the etiology for PNDs remained unclear, neuroinflammation has been characterized as one of the major causes, especially in the elderly patients. The activation of glial cells including microglia and astrocytes plays a significant role in the inflammatory responses in central nerve system (CNS). Although carefully designed, clinical studies on PNDs showed controversial results. Meanwhile, preclinical studies provided evidence from various levels, including behavior performance, protein levels, and gene expression. In this review, we summarize high‐quality studies and recent advances from both clinical and preclinical studies and provide a broad view from the onset of PNDs to its potential therapeutic targets. Future studies are needed to investigate the signaling pathways in PNDs for prevention and treatment, as well as the relationship of PNDs and future neurocognitive dysfunction. Abstract : In this review, we focused on the neuroinflammation in perioperative neurocognitive disorders (PNDs) from bench to bedside. The review not only presented the latest findings of PNDs in both clinical practice and preclinical experiment, but also pointed out useful biomarkers and potential therapeutic strategies.